Accelerated and Improved Differentiation of Retinal Organoids from Pluripotent Stem Cells in Rotating-Wall Vessel Bioreactors - DiStefano, Tyler; Chen, Holly Yu; Panebianco, Christopher; Kaya, Koray Dogan; Brooks, Matthew J.; Gieser, Linn; Morgan, Nicole Y.; Pohida, Tom; Swaroop, Anand (Stem cell reports, 2018)
Pluripotent stem cells can be differentiated into 3D retinal organoids, with major cell types self-patterning into a polarized, laminated architecture. In static cultures, organoid development may be hindered by limitations in diffusion of oxygen and nutrients. Herein, we report a bioprocess using rotating-wall vessel (RWV) bioreactors to culture retinal organoids derived from mouse pluripotent stem cells. Organoids in RWV demonstrate enhanced proliferation, with well-defined morphology and improved differentiation of neurons including ganglion cells and S-cone photoreceptors. Furthermore, RWV organoids at day 25 (D25) reveal similar maturation and transcriptome profile as those at D32 in static culture, closely recapitulating spatiotemporal development of postnatal day 6 mouse retina in vivo. Interestingly, however, retinal organoids do not differentiate further under any in vitro condition tested here, suggesting additional requirements for functional maturation. Our studies demonstrate that bioreactors can accelerate and improve organoid growth and differentiation for modeling retinal disease and evaluation of therapies. [Display omitted] •Optimization of improved retinal organogenesis using bioreactors•Better growth and differentiation of retinal neurons in bioreactor organoid culture•Recapitulation of in vivo retina development in bioreactor organoids•Requirement of additional factors for functional maturation of the retina in vitro Swaroop and colleagues demonstrate that rotating-wall vessel bioreactor culture provides a favorable environment for improved growth and differentiation of retinal organoids, closely recapitulating early stages of development in vivo.